PEM Fuel Cell Start-up/Shut-down Losses vs Temperature for Non-Graphitized and Graphitized Cathode Carbon Supports - Mittermeier, Thomas; Weiß, Alexandra; Hasché, Frédéric; Hübner, Gerold; Gasteiger, Hubert A. (Journal of the Electrochemical Society, 2017)
One of the key figures for the success of proton exchange membrane fuel cells (PEMFCs) in automotive applications is lifetime. Damage of the cathode carbon support, induced by hydrogen/air fronts moving through the anode during start-up/shut-down (SUSD), is one of the lifetime limiting factors. In this study, we examine the impact of varying the temperature at which SUSD events take place, both experimentally and by a kinetic model. For MEAs with conventional carbon supports, the model prediction of carbon oxidation reaction (COR) currents as a function of temperature matches well with the temperature dependence of experimentally determined SUSD degradation rates (predicting ≈8-fold lower COR currents compared to ≈10-fold lower measured degradation rates at 5°C compared to 80°C). This, however, is not the case for MEAs with graphitized carbon supports, where a factor of ≈39 lower COR currents are predicted when decreasing SUSD temperature from 80 to 5°C, in contrast to the measured decrease by a factor of ≈10. As we will show, this is explained by a change of the governing degradation mechanism from predominantly carbon corrosion induced losses at higher temperature to predominantly voltage cycling induced platinum surface area losses near/below room temperature.